2022
DOI: 10.3389/fnagi.2022.994130
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models identify ferroptosis-related genes as potential diagnostic biomarkers for Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a complex, and multifactorial neurodegenerative disease. Previous studies have revealed that oxidative stress, synaptic toxicity, autophagy, and neuroinflammation play crucial roles in the progress of AD, however, its pathogenesis is still unclear. Recent researches have indicated that ferroptosis, an iron-dependent programmed cell death, might be involved in the pathogenesis of AD. Therefore, we aim to screen correlative ferroptosis-related genes (FRGs) in the progress of AD to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…To further investigate the molecular mechanisms between α-syn, STAT3 and ferroptosis, we used transcriptome sequencing of control and HMC3 cells exposed to α-syn oligomers. Gene set enrichment analysis (GSEA) is widely used to implement gene set enrichment testing, which is based on mainly enriched molecular signatures rather than differential gene expression 29,30 . GSEA showed a signi cant enrichment in the ferroptosis-related gene set.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the molecular mechanisms between α-syn, STAT3 and ferroptosis, we used transcriptome sequencing of control and HMC3 cells exposed to α-syn oligomers. Gene set enrichment analysis (GSEA) is widely used to implement gene set enrichment testing, which is based on mainly enriched molecular signatures rather than differential gene expression 29,30 . GSEA showed a signi cant enrichment in the ferroptosis-related gene set.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) are involved in ferroptosis and AD progression, Tan et al (2023) identified 5 AD and ferroptosis-related hub genes, and constructed a novel ferroptosis-related signature models including mRNAs, miRNAs and lncRNAs. Deng et al (2022) screen correlative ferroptosis-related genes (FRGs) in the progress of AD by logistic regression.…”
Section: Identification Of Candidate Biomarkers Associated With the B...mentioning
confidence: 99%